GAME ONLINE DAN PENGARUHNYA TERHADAP PERILAKU INTERAKSI SOSIAL - Aprianti Aprianti; Muhammad Syafwani; Rita Kirana; Agus Rachmadi; Norida Norida (LPSDI Bina Patria, 2023)
South Kalimantan Province is ranked 23rd out of all provinces in Indonesia for internet users in 2021, namely 3,259,199 active internet users. The research carried out is an analytic research with a cross-sectional design, namely measuring or observing at the same time or observing independent and dependent variable data only once at that time. not always playing online games makes someone less good at social interaction, as in the results of this study. Based on the theory stated that special forms of social interaction are other forms of social processes. Interaction is the process of these people equally communicating and influencing each other in thought and in the form of action. This study aims to find out about online games and their influence on social interaction behavior in students of SMP Negeri 9 Banjarmasin. It is analytic in nature with a cross-sectional design, namely taking measurements or observations at the same time or observing independent and dependent variable data only once at that time. Ho is accepted, which means that there is no significant relationship between the use of online games and social interaction among students at SMP Negeri 9 Banjarmasin. Most of the respondents used mild online games as many as 61 students (76.3%) and moderate social interaction as many as 57 students. The relationship between online game users and the surrounding environment, such as school friends, neighbors, or even their own family can be said to be good, because even though they really like online games, the user interaction continues.